The Determinants Factors of Personal Mastery Among Clinical Nurse Practitioners in Indonesia - Kornelis Nama Beni; Nursalam Nursalam; M Hasinuddin; Diah Priyantini; Daviq Ayatulloh (Fundamental and Management Nursing Journal, 2024)
Introduction: Human resources of nursing who have low personal mastery have an impact on the quality and productivity of nursing services. Several factors have been studied to be associated with the low personal mastery of nurses. The purpose of this study was to analyze the factors that’s influencing personal mastery improvement of clinical nurse practitioners in a hospital. Methods: This study applied cross sectional design with 120 respondents through cluster sampling technique in one of Surabaya Hospital. Data were collected using the personal mastery factors questionnaire that has been tested for validity and reliability. The variable included training and development, leadership, attitudes, competencies, motivation, personal values, job design and personal mastery of nurses. Data were analyzed using multiple linear regression. Results: The result showed that competence, personal values and job design factors partially influenced the personal mastery (p = 0.006), (p = 0.001), (p = 0.005). Training and development, leadership, attitude and motivation have not influenced on personal mastery (p = 0.871), (p = 0.352), (p = 0.900), (p = 0.312). Simultaneously development and training, leadership, attitudes, competencies, motivation, personal values and job design factors was influenced the personal mastery of nurses' (p = 0.000). The influenced independent’s variable on personal mastery of clinical nurse practitioners is 58.1%. Conclusions: Personal mastery of clinical nurse practitioners was increased by improving the competence, strengthening of the personal values and design a good job. Further studies are warrant to examine other factors that can improve nurses' personal mastery such as organizational culture, reward systems that affect the performance of clinical nurse practitioners.